Jeda untuk Produktif: Bagaimana Cyberloafing Membantu Pengemudi Ojek Online Mengelola Stres dan Produktivitas? - Muhammad Ikhsan Alif; Prasis Damai Nursyam Hamijaya; Luh Made Wisnu Satyaninggrat; Masayu Sitti Nur Syabina; Muhammad Afdelpiero Hidayat; Uturestantix; Fitri Agustina (SPECTA Journal of Technology, 2026)
The gig economy exposes online ride-hailing drivers to a precarious work environment characterized by algorithmic control, income uncertainty, and long working hours, leading to significant job stress. This high-pressure context raises a critical research problem: how do these workers manage psychological strain to sustain performance when formal organizational support is absent? Cyberloafing, a behavior with a debated dual role as both a counterproductive act and a recovery tool, emerges as a potential, self-directed coping strategy. This study aims to examine the mediating role of cyberloafing in the relationship between job stress and productivity among online ride-hailing drivers, framed by the Conservation of Resources (COR) theory. A quantitative survey with a cross-sectional design was conducted with 199 drivers, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that job stress has a significant positive effect on cyberloafing (β = 0.29; p ≤ 0.01), which in turn has a significant positive effect on productivity (β = 0.24; p ≤ 0.01). The main finding confirms that cyberloafing acts as a full mediator, revealing that the entire influence of stress on productivity is channeled through this behavior. This re-frames cyberloafing not as a counterproductive act, but as an essential adaptive coping mechanism that helps drivers restore psychological resources under pressure, thereby maintaining productivity in a demanding, autonomous work setting.